Ethics of placebo use in randomised studies: primer for physiotherapists - N. T. Amusat (AOSIS, 2006)
Evidence based practice is driving the need to establish effectiveness of interventions employed by health professionals. The need to show effectiveness for interventions employed by physiotherapists has not been greater. This has led to an increase in the body of evidence available on physiotherapeutic methods. The quality of the evidence, however, has made it difficult to draw definitive conclusions on the effect of some of these interventions. There is therefore a call for improved methodologies in physiotherapy effectiveness studies. These needs may prompt even greater use of randomized trials with or without a placebo arm, which are regarded as the best way to show effectiveness. The use of placebo rather than an active  comparator has advantages in showing absolute effectiveness of interventions. However, there may be ethical concerns posed by its use in clinical trials. The balance is therefore required between good ethics and sound science. The goal of this article is to provide physiotherapists with a basic knowledge of the ethics of placebo use in randomized studies. This should prepare researchers to better balance ethical needs with scientific imperatives when designing effectiveness studies.